Teacher’s Roles and Students’ Behaviors in the Movie The Ron Clark’s Story - Wina Kristian (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This thesis is a qualitative study on teacher’s roles and students’ behaviors in the movie The Ron Clark’s Story. The objectives of this study are to find out the teacher’s roles and students’ behaviors toward the teacher’s roles in the classroom scenes. This study was based on Harmer’s theory on teacher’s roles (2001, 2007) and Scarlett’s theory on students’ behaviors (2015). The data were collected from the movie and transcript of the conversation in the movie focusing on all of the classroom scenes. The findings show that the teacher applies six out of eight teacher’s roles: prompter, controller, resource, organizer, tutor, and participant. The findings of the students’ behaviors show that the students’ behaviors toward the teacher’s roles in the classroom are mostly having disruptive behaviors from scene one to four until it is starting to have significant changes to positive behaviors from scene five to eleven. Keywords: Teacher’s Roles, Students’ Behaviors, The Ron Clark’s Story